Association of atrophy of the medial temporal lobe with reduced blood flow in the posterior parietotemporal cortex in patients with a clinical and pathological diagnosis of Alzheimer's disease. Issue 3 (March 1992) - Jobst, K A; Smith, A D; Barker, C S; Wear, A; King, E M; Smith, A; Anslow, P A; Molyneux, A J; Shepstone, B J; Soper, N
Abstract : A combination of medial temporal lobe atrophy, shown by computed tomography, and reduced blood flow in the parietotemporal cortex, shown by single photon emission tomography, was found in 86% (44/51) of patients with a clinical diagnosis of senile dementia of the Alzheimer type (SDAT). The same combination of changes was found in four out of 10 patients with other clinical types of dementia and in two out of 18 with no evidence of cognitive deficit. Of the 12 patients who died, 10 fulfilled histopathological criteria for Alzheimer's disease, nine of them having a clinical diagnosis of SDAT, and one a clinical diagnosis of multi-infarct dementia. All 10 patients with histopathologically diagnosed Alzheimer's disease had shown a combination of hippocampal atrophy and reduced parietotemporal blood flow in life. In 10 patients (nine with SDAT) out of 12 in whom the hippocampal atrophy was more noticeable on one side of the brain than on the other the parietotemporal perfusion deficit was also asymmetrical, being greater on the side showing more hippocampal atrophy. These results suggest that the combination of atrophy of the hippocampal formation and reduced blood flow in the parietotemporal region is a feature of dementia of the Alzheimer type and that the functional change in the parietotemporal region might be related to the loss of the projection neurons in the parahippocampal gyrus that innervate this region of the neocortex.